KEAMANAN CYBER DITERAPKAN UNTUK SEKTOR KEUANGAN DI INDONESIA - Sidik, Machfud (Jurnal Pajak dan Bisnis, 2020)
This paper discusses supervisory issues that underlie potential developments and risks in Cyber ??security that are applied to the financial industry. World attacks on financial institutions and financial market infrastructure are increasingly widespread and more sophisticated. Cybercrime is a growing threat in the virtual world because individuals and financial sector organizations rely more on the internet at increasingly accelerating speeds